GENERAL ANESTHESIA The Effect of COVID-19 on General Anaesthesia Rates for Caesarean Section. A Cross-sectional Analysis of 6 Hospitals in the North-west of England. Issue 1 (March 2022) - Bhatia, K.; Columb, M.; Bewlay, A.; Eccles, J.; Hulgur, M.; Jayan, N.; Lie, J.; Verma, D.; Parikh, R.
Abstract : ( Anaesthesia . 2021;76:312–319. doi: 10.1111/anae.15313. Epub November 2, 2020) Before the onset of the COVID-19 (SARS-CoV-2) global pandemic, data from the National Obstetric Anaesthesia Database suggests that regional anesthesia (RA), as opposed to general anesthesia (GA), was used in 91% of all cesarean deliveries (CD) performed. In the time since COVID-19 emerged, there is evidence that regional anesthesia has been encouraged over general anesthesia in the surgical setting, including during CD. Benefits to regional anesthesia include limiting the need for aerosol-generating procedures and consequential risks on healthcare staff, decreasing the use personal protective equipment (PPE), and increasing surgical theatre turnover efficiency. There is limited information on the impact anesthesia-specific guidelines have had on actual RA and GA rates for CD during the pandemic. This study investigates changes in CD general anesthesia rates occurring during the first peak of the pandemic across six maternity units within north-west England.